Copper Acts Synergistically With Fluconazole in Candida glabrata by Compromising Drug Efflux, Sterol Metabolism, and Zinc Homeostasis - Gaspar-Cordeiro, Ana; Amaral, Catarina; Pobre, Vânia; Antunes, Wilson; Petronilho, Ana; Paixão, Paulo; Matos, António P.; Pimentel, Catarina (Frontiers in Microbiology, 2022)
The synergistic combinations of drugs are promising strategies to boost the effectiveness of current antifungals and thus prevent the emergence of resistance. In this work, we show that copper and the antifungal fluconazole act synergistically against Candida glabrata, an opportunistic pathogenic yeast intrinsically tolerant to fluconazole. Analyses of the transcriptomic profile of C. glabrata after the combination of copper and fluconazole showed that the expression of the multidrug transporter gene CDR1 was decreased, suggesting that fluconazole efflux could be affected. In agreement, we observed that copper inhibits the transactivation of Pdr1, the transcription regulator of multidrug transporters and leads to the intracellular accumulation of fluconazole. Copper also decreases the transcriptional induction of ergosterol biosynthesis (ERG) genes by fluconazole, which culminates in the accumulation of toxic sterols. Co-treatment of cells with copper and fluconazole should affect the function of proteins located in the plasma membrane, as several ultrastructural alterations, including irregular cell wall and plasma membrane and loss of cell wall integrity, were observed. Finally, we show that the combination of copper and fluconazole downregulates the expression of the gene encoding the zinc-responsive transcription regulator Zap1, which possibly, together with the membrane transporters malfunction, generates zinc depletion. Supplementation with zinc reverts the toxic effect of combining copper with fluconazole, underscoring the importance of this metal in the observed synergistic effect. Overall, this work, while unveiling the molecular basis that supports the use of copper to enhance the effectiveness of fluconazole, paves the way for the development of new metal-based antifungal strategies.